2010
DOI: 10.1029/2008ja013839
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting low‐latitude radio scintillation with 3‐D ionospheric plume models: 1. Plume model

Abstract: [1] A three-dimensional model has been developed for the plasma plumes caused by interchange instabilities in the low-latitude ionosphere to describe the structure and extent of the radio scintillation generated by turbulence in and around the plumes (down to the scale sizes resolvable by the computer model). With the inclusion of the processes that determine the transport of plasma parallel to the geomagnetic field lines as well as transverse to them, the model can predict the extent in latitude of the plumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 68 publications
8
128
1
Order By: Relevance
“…The large spiky upward velocities after 19:00 LT were the plasma drift driven by polarization electric fields inside the plasma bubbles, and the downward spiky velocities were associated with the dense plasma between the bubbles. The large upward plasma drift inside plasma bubbles and relatively small downward drift between bubbles were reproduced by numerical simulations [Scannapieco and Ossakow, 1976;Zalesak et al, 1982;Huang and Kelley, 1996;Huba et al, 2009;Retterer, 2010].…”
Section: Observationsmentioning
confidence: 84%
“…The large spiky upward velocities after 19:00 LT were the plasma drift driven by polarization electric fields inside the plasma bubbles, and the downward spiky velocities were associated with the dense plasma between the bubbles. The large upward plasma drift inside plasma bubbles and relatively small downward drift between bubbles were reproduced by numerical simulations [Scannapieco and Ossakow, 1976;Zalesak et al, 1982;Huang and Kelley, 1996;Huba et al, 2009;Retterer, 2010].…”
Section: Observationsmentioning
confidence: 84%
“…Data from a suite of sensors on board the satellite drive an equatorial ionospheric model to forecast the onset of plasma instability, as well as its evolution into plasma bubbles (Retterer, 2010). Due to its orbital period, these sensors are able to revisit neighbor regions in space at 90 min intervals, measuring different ionospheric parameters with high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…We are unable to determine which bottomside depletion becomes a topside plume or if the bottomside features merged to form one plume since the topside plume is as wide as the group of depletions. Equatorial spread F plumes are not expected to have the same width at all altitudes and can be wider at higher altitudes (e.g., Retterer, 2010). We have looked at other cases and have found that we only observe one topside plume associated with a group of bottomside depletions.…”
Section: Higher-latitude Esf Effectsmentioning
confidence: 86%